The effects of the hexagonal boron nitride nanoflake properties on the thermal conductivity of hexagonal boron nitride nanoflake/silicone rubber composites. (December 2019) - Zhong, Bo; Zou, Jiaxin; An, Lulu; Ji, Chengyu; Huang, Xiaoxiao; Liu, Wei; Yu, Yuanlie; Wang, Huatao; Wen, Guangwu; Zhao, Kun; Lin, Xuesong
Abstract: Hexagonal boron nitride nanoflakes ( h -BNNFs) are usually selected as fillers to improve the thermal conductivity of polymer materials. However, previous research mainly focused on the influence of h -BNNF content and orientation. In this report, the effects of the content, geometry, thickness, modification and orientation of h -BNNFs on the thermal conductivity of h -BNNF/polymer composites were systematically investigated based on the h -BNNF/silicone rubber ( h -BNNF/SR) composites. The thermal conductivity of h -BNNF/SR composites increased tremendously with the increase of h -BNNF content. Meanwhile, the h -BNNF contents also show great effects on the viscosity, hardness and thermal stability of the composites, and the h -BNNF content of 20% is more advantageous for processing and application of the composites. Besides, modified, flake-like and thinner h -BNNFs can result in better reinforcement in thermal conductivity than unmodified, agglomerated and thicker ones. h -BNNF/SR composites with shear force induced oriented h -BNNFs showed further enhanced thermal conductivity, and the composite with 40 wt% oriented h -BNNFs exhibits the best thermal conductivity of 0.901 W/(m K).